Analyzing an Unconventional Success Story Chick-fil-A Fast Food Restaurants in the USA - Manko, Barbara A. (Zielona Góra: Faculty of Economics and Management Press)
The U.S. fast-food chain Chick-fil-A, Inc. has prospered financially and scored multiple rankings at or near the top of its industry by using unconventional management practices, including some that appear to be drawbacks. This paper attempts what previous academic research has not: a thorough analysis of Chick-fil-A`s practices and policies, looking at how they might function as ?success factors? and how the company has turned apparent disadvantages into advantages.
Keywords: Chick-fil-A; fast food restaurant; quick service restaurant; customer service; social media; employees; customer; American restaurants; franchised restaurant; employee satisfaction; management practice